IEEE Information Theory Workshop 2010 (ITW 2010) 2010
DOI: 10.1109/itwksps.2010.5503180
|View full text |Cite
|
Sign up to set email alerts
|

Remarks on the criteria of constructing MIMO-MAC DMT optimal codes

Abstract: Abstract-In this paper we investigate the criteria proposed by Coronel et al. for constructing MIMO MAC-DMT optimal codes over several classes of fading channels. We first give a counterexample showing their DMT result is not correct when the channel is frequency-selective. For the case of symmetric MIMO-MAC flat fading channels, their DMT result reduces to exactly the same as that derived by Tse et al. , and we therefore focus on their criteria for constructing MAC-DMT optimal codes, especially when the numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 9 publications
1
17
0
Order By: Relevance
“…Using the geometrical argument, we showed that the outage bound in [1] is not limiting for the outage probability as claimed in [6]. Moreover, a new family of split NVD parallel codes to achieve the optimal DMT in [5] for the case of time or frequency selective channels is proposed.…”
Section: Discussionmentioning
confidence: 97%
“…Using the geometrical argument, we showed that the outage bound in [1] is not limiting for the outage probability as claimed in [6]. Moreover, a new family of split NVD parallel codes to achieve the optimal DMT in [5] for the case of time or frequency selective channels is proposed.…”
Section: Discussionmentioning
confidence: 97%
“…Some progress in these questions has been made in [4], [3], [2], and it is easy to believe that a condition expressed in terms of the decay function is also out there [4]. In this note we state some interesting results from [5] about the available decay functions of all MU-MIMO lattice codes in general. Based on them, and as the main contribution of this paper, we study in particular the decay function of the code proposed by Badr & Belfiore (BB-code, in short).…”
Section: Background and The Decay Functionmentioning
confidence: 94%
“…This corresponds to a MIMO MAC space-time code, which are known ( [11], [15]) to perform well and to achieve the socalled diversity-multiplexing gain tradeoff (DMT) [10], when the field is chosen well. With sufficient SNR, the receiver is able to decode the message with very high probability and gets b , c , which he can map back to bit strings b, c = a + b and further reveal a = b + (a + b).…”
Section: Space-time Storage Codes Over Macmentioning
confidence: 99%
“…As the channel quality is imposed by nature, we will concentrate on designing the space-time code as well as possible. To this end, the ST code C ST consisting of a finite number of the matrices (1) should have the following property that we recite from [15].…”
Section: Design Criteria For Space-time Storage Codesmentioning
confidence: 99%